1995
DOI: 10.1109/77.403193
|View full text |Cite
|
Sign up to set email alerts
|

Electric field effect in Sm/sub 1-x/Ca/sub x/Ba/sub 2/Cu/sub 3/O/sub y/ bicrystal junctions

Abstract: A bstract-A three terminal device was fabricated by depositing a thin film of Ca-doped SmBa2Cu30y on a bicrystal SrTi03 substrate and then structuring a gate over the resulting junction.The channel shows RSJ-like Josephson junction behavior. By applying a voltage to the gate, a large electric field effect was observed. The largest field effect was observed in films where 30% of the Sm was replaced by Ca. The critical current of the junction was modulated 23% by the application of an electric field of 5~1 0~ V/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…Furthermore gated Josephson junctions can be used as Josephson field-effect transistors ͑JOFETs͒. Dong et al 6 and Peterson et al 7 fabricated bicrystal JOFET devices using, like Ivanov, a metal-insulator-superconductor FET ͑MISFET͒ structure, but with underdoped Sm 1Ϫx Ca x Ba 2 Cu 3 O y and ultrathin YBCO films as superconducting channels, respectively. 2 In recent years, high-T c superconductors have been used for the fabrication of JOFETs.…”
mentioning
confidence: 99%
“…Furthermore gated Josephson junctions can be used as Josephson field-effect transistors ͑JOFETs͒. Dong et al 6 and Peterson et al 7 fabricated bicrystal JOFET devices using, like Ivanov, a metal-insulator-superconductor FET ͑MISFET͒ structure, but with underdoped Sm 1Ϫx Ca x Ba 2 Cu 3 O y and ultrathin YBCO films as superconducting channels, respectively. 2 In recent years, high-T c superconductors have been used for the fabrication of JOFETs.…”
mentioning
confidence: 99%
“…Our aim in this paper is to apply this method to the field efffect modulations seen in the JoFETs of Ref. [3,4]. We demonstrate that the JoFET systems can be fit into the same conceptual framework as the YBa 2 Cu 3 O 7−δ grain boundaries.…”
mentioning
confidence: 99%
“…Dong et al [3,4] showed that there is a 23% modulation of the critical current on a grain boundary of a 50 nm thick channel of Sm 1−x Ca x Ba 2 Cu 3 O y (Ca-SBCO). Nakajima et al [7] reported a 5% modulation of critical current on a 60 nm thick YBCO grain boundary junction channel which can be described by a parallel resistor model.…”
mentioning
confidence: 99%
See 2 more Smart Citations